DETERMINATION OF THE OPTIMAL OZONATION MODE FOR WINTER GARLIC PLANTING MATERIAL - Пугач, С.Г.; Pugach, S.; Завада, Л.М.; Zavada, L.; Замурієв, О.; Zamuriev, О.; Кудін, Д.В.; Kudin, D.; Опалєв, П.О.; Opalev, P.; Мельник, А.В.; Melnyk, А.; et al. (Національный науковий центр "Харківський фізико-технічний інститут", 2021)
Дослідження проведено у Інституті овочівництва і баштанництва НААН України та відділі Низькотемпературної не- рівноважної плазмохімії ННЦ «Харківський фізико-технічний інститут» НАН України на сортах часнику озимого «Дю- шес» та «Мереф’янський білий». Передсадивну обробку здійснено за 3-5 діб до садіння за допомогою озонатора серії OzW StreamOzone TM у чотириразовому повторенні. Лабораторні дослідження щодо розвитку грибних хвороб родів Fusarium та Penicillium на обробленому матеріалі виконували з використанням вологих камер у чотириразовому повто- ренні. Досліджено вплив концентрацій озону 10, 50 та 100 ppm O3 та часу експозиції – 10, 100 та 180 хв на ураженість часнику чорною і зеленою пліснявою. The study was carried out at the Institute of Vegetable and Melon Farming of the National Academy of Agrarian Sciences of Ukraine and the Department of Low-Temperature Non-equilibrium Plasma Chemistry of the NSC "Kharkov Institute of Physics and Technology" of the National Academy of Sciences of Ukraine using the varieties of winter garlic, such as Duchess and Merefyanskiy white. Pre-plant treatment with four-time repeatability was carried out 3-5 days before planting using an OzW Stream Ozone TM ozone generator. Laboratory studies of fungal diseases Fusarium and Penicillium progress on the treated material were carried out with four-time repeatability in wet chambers. The effect of ozone concentration of 10, 50, and 100 PPM and exposure time of 10, 60, and 180 min on infestation of garlic with black and green mold was studied.
Визначення оптимального режиму озонування озимого часнику
Keywords: сорти часнику; varieties of garlic; грибні хвороби; fungal diseases; озон; ozone